2002
DOI: 10.1016/s0166-445x(01)00231-4
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and distribution of dietary nickel in lake whitefish (Coregonus clupeaformis)

Abstract: Benthic-feeding fish residing in Ni-contaminated systems are exposed to Ni through ingestion of contaminated food items and sediments. Lake whitefish (Coregonus clupeaformis) were fed diets at a ration of 0.5% of body weight three times a week containing 0, 10, 100, and 1000 microg Ni/g (as NiSO(4)) for 10, 31, and 104 days. Stomach, pyloric caeca, intestine, kidney, liver, gall bladder, gonad, gill, bone, muscle, skin, and scales were analyzed to evaluate the accumulation and distribution of Ni. Fish fed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 23 publications
4
11
0
1
Order By: Relevance
“…This may be due to the increase of heavy metals in the drainage waters, decomposition of organic matter and discharge remnants of fertilizer factories and other chemicals lead to this fact, the uptake of metals is influenced by many factors including fish species, age, and type of fish organs, season and various environmental factors. This findings agree with Nagdi & Shaker (1998); Ptashynski & Klaverkamp (2002); El-Serafy et al (2003a) and Ghanem (2006&2014) whom attributed the increase of metals during hot seasons to the effect of temperature and winds on the solubility and distribution of these metals and differ with Yacoub and Gad (2012) whom mentioned that, cold season exhibited the high level of these metals than the hot one. On the other hand, El-Serafy et al (2003b) concluded that no markedly seasonal variations in the concentration of metals in Patella Caerulea lived in polluted areas of Alexandria Coast were detected.…”
Section: Results and Discussion Heavy Metals Determinationssupporting
confidence: 87%
“…This may be due to the increase of heavy metals in the drainage waters, decomposition of organic matter and discharge remnants of fertilizer factories and other chemicals lead to this fact, the uptake of metals is influenced by many factors including fish species, age, and type of fish organs, season and various environmental factors. This findings agree with Nagdi & Shaker (1998); Ptashynski & Klaverkamp (2002); El-Serafy et al (2003a) and Ghanem (2006&2014) whom attributed the increase of metals during hot seasons to the effect of temperature and winds on the solubility and distribution of these metals and differ with Yacoub and Gad (2012) whom mentioned that, cold season exhibited the high level of these metals than the hot one. On the other hand, El-Serafy et al (2003b) concluded that no markedly seasonal variations in the concentration of metals in Patella Caerulea lived in polluted areas of Alexandria Coast were detected.…”
Section: Results and Discussion Heavy Metals Determinationssupporting
confidence: 87%
“…Therefore, the liver is considered as one of the major metal bioaccumulation organs [10]. Histopathological lesions of liver proved to be the most sensitive and reliable indicators of metal exposure [11]. …”
Section: Resultsmentioning
confidence: 99%
“…Уміст нікелю у природних водах визначається складом порід, крізь які проходить вода. Може потрапляти у водойми із ґрунтів, у результаті розкладання відмерлих рослинних і тваринних організмів, а також зі стічними водами цехів нікелювання, заводів синтетичного каучуку, нікелевих збагачувальних фабрик і з атмосферними опадами (Ptashynski and Klaverkamp, 2002;Cavani, 2005;Borbely and Nagy, 2009).…”
Section: результати та їх обговоренняunclassified